Mobile application of mental arithmetic fun-oriented learning - Pang, Sia Lee, 1990-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Project Paper (Sarjana Muda Sains Komputer (Perisian Grafik dan Multimedia)) - Universiti Teknologi Malaysia, 2014